Descriptive analysis - predictors of attitude towards purchasing halal skin care products / Azreen Jihan and Rosidah Musa - Jihan, Azreen; Musa, Rosidah (Penerbit UiTM (UiTM Press), 2017)
The purpose of this paper is to discuss the percentage of frequencies with measures of central tendency (mean value) and dispersion (standard deviation) of predictors of attitude, namely, spiritual intelligence, spiritual congruence, product image and product involvement of halal skin care products towards a continuous intention to purchase. The primary objective of the descriptive analysis is to explore and gain an initial understanding and get the feel of the data gathered from the survey. It was based upon a representative sample of adult urban Muslim career woman (users and non-users) who work or live in the target area for this study. These areas are the federal territory of the Klang Valley which are considered urbanised. The survey reached 449 adults, achieving 100 percent of the target sample size of 400. The respondents involved are those who have experience in purchasing and continue to purchase the halal skin care products. The quota sampling technique was employed. Two demographic variables have been determined as a mechanism to control the composition of the sample (gender and age).